Collaborative peer validation of a harmonized SPME-GC-MS method for analysis of selected volatile compounds in virgin olive oils. (May 2022) - Aparicio-Ruiz, Ramón; Ortiz Romero, Clemente; Casadei, Enrico; García-González, Diego L.; Servili, Maurizio; Selvaggini, Roberto; Lacoste, Florence; Escobessa, Julien; Vichi, Stefania; Quintanilla-Casas, Beatriz; Golay, Pierre-Alain; Lucci, Paolo; et al.
Abstract: The requirement for developing an instrumental method for analysis of volatile compounds responsible for the aroma that supports the work of the sensory panel test of virgin olive oils is a matter of great importance. In this paper, five laboratories participated in a collaborative study within the EU H2020 OLEUM project to develop a peer interlaboratory study of a harmonized SPME-GC-MS method for determination of volatile compounds in virgin olive oil responsible for positive attributes (e.g. fruity) and the main sensory defects. Linearity (R 2  > 0.94) and repeatability (mean relative standard deviation, RSD% = 7.60%) were satisfactory. Reproducibility results were uneven depending on the compound. The lowest RSD% values were found for ( Z )-3-hexenyl acetate (19.19%), 1-hexanol (13.26%), and acetic acid (17.47%). The limits of quantification were <0.07 mg/kg for all compounds except for ( E )-2-decenal and pentanoic acid. The study of different quantification methods revealed that the correction of the calibration curves using the internal standard led to a slightly worse repeatability, but better accuracy and reproducibility. The results obtained by five laboratories are preparatory towards a trial proper validation study, already planned in OLEUM project, involving external labs participating on a voluntary basis. Highlights: A SPME-GC-MS based protocol with 3 possible quantification methods was developed. A peer-interlab study was carried out (5 labs, 18 volatiles, 15 virgin olive oils). Results were compared with a similar study carried with FID detector. Linearity, recovery, precision and repeatability were satisfactory. Three compounds showed reproducibility RSD >40%, partially due to high LOQs.